Respuesta :
Answer:
[tex]\frac{-55}{63}[/tex]
Step-by-step explanation:
[tex]=\frac{2}{21}(\frac{-3}{13})-\frac{7}{9}-\frac{2}{21}(\frac{10}{13})[/tex]
[tex]=\frac{-2}{91}-\frac{7}{9}-\frac{2}{21}(\frac{10}{13})[/tex]
[tex]=\frac{-2}{91} +\frac{7}{9} -\frac{2}{21} (\frac{10}{13})[/tex]
[tex]=\frac{-655}{819}-\frac{2}{21} (\frac{10}{13} )[/tex]
[tex]=\frac{-655}{819}-\frac{20}{273}[/tex]
[tex]=\frac{-55}{63}[/tex]
Answer:
[tex]\frac{-55}{63}[/tex] is the answer for the question.
Step-by-step explanation:
All you have to do is just simplify the expression And you'll get your answer as [tex]\frac{-55}{63}[/tex]
Hope this helped you !